E-leadership in Effective Higher Education Management - Sunaengsih, Cucun; Maulana, Maulana; Djuanda, Dadan; Rosalin, Elin; Thahir, Muthahharah; Nurafifah, Tias Siti (Universitas Pendidikan Indonesia, 2024)
Effective leadership and management influence the institution's progress, especially in higher education. However, e-leadership and effective university management have not been fully maximized in higher education. This study aims to determine the general overview of e-leadership, effective university management, and e-leadership design ineffective university management at the UPI Sumedang Campus. This study uses a quantitative approach by using a survey method aimed at 204 UPI Sumedang Campus students. The study results show that the general picture of UPI Sumedang Campus leaders has a high e-leadership attitude by meeting the e-leadership indicators, which include visionary, convener, team sponsor, manager, innovator, and mentor to the maximum. Higher education management has been implemented effectively by meeting the indicators of the implementation of strong educational leadership by university leaders. The design of e-leadership ineffective university management has been implemented effectively, and UPI Sumedang Campus's leadership has a high e-leadership attitude. This research is expected to contribute to higher education by allowing leaders to make more specific and strategic decisions in improving the implementation of the education system, which, in turn, will impact improving the overall quality of higher education.